Modal Intelektual (Intellectual Capital) dan Nilai Perusahaan Pada Industri Manufaktur - Gita Puspita; Tri Wahyudi (Politeknik Ganesha Medan, 2021)
Information about company value and intellectual capital is important information to be known by investors. This research aimed to find out the influence of intellectual capital against the value of the company's of manufacturing companies listed on the Indonesia stock exchange year 2014 – 2017. This type of research is quantitative research. This population includes all manufacturing companies listed on the Indonesia stock exchange and obtained samples of as many as 17 companies. Based on the results of research, partially Value Added Capital Employed (VACA) and Value Added Intellectual Coefficient (VAIC) have an effect on company value (Tobin's Q). Value Added Human Capital (VAHU) and Value Added Structural Capital (STVA) have no effect on company value (Tobin's Q). Based on the suitability test of Value Added Capital Employed (VACA) models, Value Added Human Capital (VAHU), Value Added Structural Capital (STVA), and Intellectual Capital were proxied by Value Added Intellectual Coefficient (VAIC) simultaneously has an effect on Company Value (Tobin's Q). From the result of this research, investors in order to make intellectual capital as a consideration before making investment decisions because better company value will show better growth prospects so as to provide prosperity for investors and shareholders.